Implementasi Forward Chaining pada Sistem Pakar Kerusakan Mesin Fotocopy - Kurniawan, Ferdian Miko; Christanto, Febrian Wahyu; Ahmad Firdaus, Eryan; Rohayati, Tuti (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2024)
The Forward Chaining method is used in developing an expert system to diagnose photocopier damage. This system aims to help technicians or non-technical users identify and repair problems that occur with photocopiers. The system collects information about symptoms or signs associated with damage to the photocopier. This information is then used to check existing rules in the knowledge base. The system sequentially checks these rules and matches the conditions to the symptoms observed on the copier. Therefore, this research aims to implement the forward chaining method in a website-based Canon IRA 4251/6275 photocopier damage expert system as a solution to help technicians so that they do not need to come to the customer's place to repair the photocopier, because customers can repair damage to their photocopier accordingly. The directions from the expert system application are useful for reducing costs by 70% for calling a photocopy technician. These results were obtained from the user questionnaire answers that this application was very helpful. The research method used is the case study method, by collecting data through interviews and observation. And the development method here uses the prototype method. This expert system application uses the CodeIgniter framework and uses a MySQL database. The application for implementing forward chaining on the website-based Canon IRA 4251/6275 photocopier damage expert system is expected to help customers solve problems related to damage to photocopiers and reduce customer costs for servicing photocopiers.